Notariusz jako organ ochrony prawnej w świetle prawa polskiego i prawa Unii Europejskiej - Setkowicz, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The paper aims to examine the role of a notary as a legal protection authority in Polish and European Union law systems. The European Union Regulation on Succession has changed the existing role of a notary. It has established the new institution of legal protection — a European Certificate of Succession. The competence to issue a European Certificate of Succession has been entrusted to the notaries beside the courts. This new notarial action has direct effect in the other Member States of the European Union. The scope of legal protection exercised by a notary went beyond national borders and its role has become cross-border.
Keywords: notariusz; ochrona prawna; polskie prawo; prawo europejskie